Grain bread - Z. M. Kunasheva; M. K. Kodzokova (Новые технологии, 2019)
Cereal products are the primary source of nutrition for the population. From ancient times to the present humanity has been engaged in growing wheat as a food crop. Salt-free cakes were the first products, and today the range of bakery products includes thousands of items. Bread and bakery products form the basis of the material well-being of the world's population and they possess a wide range of nutrients. In a daily diet they are easily digestible and do not pall. Cereal products from grain crops contribute to meeting the human needs of calories to a considerable extent, being source of protein, fiber, vitamins of group B. The modern concept of healthy nutrition is based on the inclusion of safe, biologically pure balanced products in the diet. Due to the rapid deterioration of the ecology of our planet, modern food production manufactures baking flour of unstable quality. Properties and basic quality indicators of different flour batches are different and do not even meet the requirements of NTD, which contributes to the deterioration of the quality of the finished bread. All this has an adverse effect on the health of the population of the entire planet. Thus, as bread is a product of daily consumption, there is a need to increase its nutritional value and use environmentally friendly raw materials in production technologies. The article discusses the relevance of improving the nutritional value of bakery products and the use in technologies and recipes for the production of environmentally friendly raw materials, in particular, instead of whole wheat flour.